2013
DOI: 10.1371/journal.pone.0084768
|View full text |Cite
|
Sign up to set email alerts
|

Microcystin-LR Induced Reactive Oxygen Species Mediate Cytoskeletal Disruption and Apoptosis of Hepatocytes in Cyprinus carpio L.

Abstract: Microcystins (MCs) are a group of cyclic hepatotoxic peptides produced by cyanobacteria. Microcystin-LR (MC-LR) contains Leucine (L) and Arginine (R) in the variable positions, and is one of the most common and potently toxic peptides. MC-LR can inhibit protein phosphatase type 1 and type 2A (PP1 and PP2A) activities and induce excessive production of reactive oxygen species (ROS). The underlying mechanism of the inhibition of PP1 and PP2A has been extensively studied. The over-production of ROS is considered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 36 publications
2
24
0
Order By: Relevance
“…Our previous study also showed that pre-treatment of BSO enhanced the level of oxidative stress and promoted MC-induced apoptosis [55]. MCinduced oxidative stress and apoptosis were also observed in studies on aquatic animals both in vivo [73][74][75] and in vitro [56,[76][77][78].…”
Section: Oxidative Stressmentioning
confidence: 69%
See 2 more Smart Citations
“…Our previous study also showed that pre-treatment of BSO enhanced the level of oxidative stress and promoted MC-induced apoptosis [55]. MCinduced oxidative stress and apoptosis were also observed in studies on aquatic animals both in vivo [73][74][75] and in vitro [56,[76][77][78].…”
Section: Oxidative Stressmentioning
confidence: 69%
“…These elements not only provide cellular architecture to maintain cell shape, cell division, migration, adhesion and contraction/relaxation, but also play a central role in signal transduction. Both in vivo and in vitro studies have shown that exposure of human, rat and fish hepatocytes to MC-LR induce alteration, aggregation, breakdown, reorganization and collapse of the cytoskeleton, loss of intercellular contacts and consequently disruption of cellular architecture [75,[100][101][102]. Cytoskeletal alterations induced by MC-LR were also reflected in plants, Vicia faba [103] and Ceratophyllum demersum [104].…”
Section: Cytoskeleton Disruptionmentioning
confidence: 99%
See 1 more Smart Citation
“…These toxic MCs are primarily accumulated in the liver and mediated by organic anion transporters, such as members of the OATP superfamily which are highly expressed in hepatocytes (Fischer et al, 2005). Upon entry into cells, MCs specially bind to and inhibit protein phosphatases 1 and 2A (PP-1 and PP2A) (MacKintosh et al, 1990) and can increase the formation of reactive oxygen species (ROS) (Nong et al, 2007;Jiang et al, 2013), thereby influencing the regulation of cellular protein phosphorylation and finally cause loss of liver architecture, dysfunction and necrosis (Cazenave et al, 2006). P-glycoproteins are versatile efflux transporters for a wide range of substrates with broad specificity, including endo-and exogenous hydrophobic amphipathic compounds such as physiological metabolites, therapeutic drugs and toxic xenobiotics (Sharom, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…These elements exert a wide range of impacts on reproductive events including sperm maturation and motility, oocyte maturation, fertilization and early embryo development [116]. It has been documented that both protein phosphatase inhibition and oxidative stress induced by MCs may lead to cytoskeletal damage [117][118][119][120][121][122]. Gácsi et al [77] showed that apoptotic shrinkage in Chinese hamster ovary (CHO-K1) cells was associated with the shortening and loss of MFs and with a concentration-dependent depolymerization of MTs.…”
Section: Cytoskeleton Disruptionmentioning
confidence: 99%